Principles of environmental science :Inquiry and Applications - Cunningham, William P.; Cunningham, Mary Ann. ([S.l.] : McGraw-Hill Science/Engineering/Math, 2003)
As environmental science textbooks have gotten larger and more encyclopedic over the years, an increasing number of instructors have called for a smaller, less expensive book that concentrates on the core principles of the discipline. "Principles of Environmental Science: Inquiry and Applications" emphasizes how science can help us find solutions for important environmental issues. While not attempting to describe every possible environmental dilemma or scientific field of study, this text focuses on the major topics we face and how scientists search for answers to questions about them. Students are provided a solid grounding in scientific principles and then encouraged to think analytically and creatively on their own.
Keywords: environmental science